A Case Study in Successful Progressive Design Build Tunneling - RETC2023 - Leo C. Weiman-Benitez; Nik Sokol; Mike Jaeger (Society for Mining, Metallurgy & Exploration, 2023)
Silicon Valley Clean Water signed a progressive-design-build (PDB) contract with Barnard Bessac Joint Venture (BBJV) to design and construct the Gravity Pipeline tunnel in Redwood City, CA. Owner and Design-Builder teamed with designer Arup to provide a final product: 3.3 miles of 182 in. O.D. precast concrete segmentally lined tunnel with 10 ft. and 11 ft. I.D. Fiberglass Reinforced Polymer Mortar (FRPM) carrier pipe, complete with two FRPM Drop Structures. BBJV and Arup collaborated with SVCW to evaluate alternative design concepts, negotiate an agreeable price and reduce contingencies through a transparent estimating process, and deliver the project ahead of schedule.